مراسيل مصنف عبد الرزاق فى كتاب المغازي وأهل الكتاب : جمعا ودراسة نقدية - علي، مختار (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study investigates the issue of ahadith that were incompletely transmitted (mursal) in chapters of People of the Book and the military expeditions led by the Prophet (PBUH) from al-Musnnaf of Abdul Razzaq al-Sanani. Four areas were thoroughly investigated. Firstly, the life of Abdul Imam Razzaq in terms of his lineage, abirth, teachers, students, publications and date of death were studied. Secondly, critical study of his book, al-Musannaf, which presents the author's literal and technical introduction, regulating the book and its reference to the author and explaining the content of the book is conducted. Thirdly, investigating the incompletely transmitted ahadith, whereby their literal and technical definitions, types, levels and how they were used by scholars as evidence are highlighted. Finally, examining the incompletely transmitted ahadith from the beginning of the chapter that discusses military expeditions led by the Prophet (PBUH) through the end is done. Introducing the chain of transmitters is also performed, then examining the ahadith, followed by other supporting details and finally stipulating the chain of the ahadith. Both analytical and inductive approaches are used to confirm the level of the ahadith according to requirements made by the science of hadith. The study unveils anumber of findings. Most importantly is that the majority of these ahadith could progress to the category of good by virtue of other ahadith. Conversely, there are afew of these ahadith that cannot progress to the foregoing category. It is worth mentioning that Imam Abdul Razzaq is a firm authority in the eyes of hadith scholars, and that his book, al-Musannaf is one of the important sources on prophetic hadith. Furthermore, the study puts forward some recommendations which could help bridge the gaps pertaining to some issues of the sciences of hadith, such as examining the remaining chapters of this book.